2013
DOI: 10.1186/1756-9966-32-88
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and clinical advantages of deep inspiration breath-hold (DIBH) during radiotherapy of breast cancer

Abstract: BackgroundTo investigate the potential dosimetric and clinical benefits of Deep Inspiration Breath-Hold (DIBH) technique during radiotherapy of breast cancer compared with Free Breathing (FB).MethodsEight left-sided breast cancer patients underwent a supervised breath hold during treatment. For each patient, two CT scans were acquired with and without breath hold, and virtual simulation was performed for conventional tangential fields, utilizing 6 or 15 MV photon fields. The resulting dose–volume histograms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
94
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 28 publications
16
94
1
2
Order By: Relevance
“…• Technika wstrzymywania oddechu w fazie głębokiego wdechu, inaczej bramkowania oddechowego, umoż-liwiająca osłonięcie serca przed polami stycznymi i zmniejszenie napromienienia narażonych narządów bez niekorzystnego wpływu na kliniczną objętość docelową [294].…”
Section: Radioterapiaunclassified
“…• Technika wstrzymywania oddechu w fazie głębokiego wdechu, inaczej bramkowania oddechowego, umoż-liwiająca osłonięcie serca przed polami stycznymi i zmniejszenie napromienienia narażonych narządów bez niekorzystnego wpływu na kliniczną objętość docelową [294].…”
Section: Radioterapiaunclassified
“…The DIBH method physically increases the separation between the heart/LAD and the target volume to reduce the irradiated heart volume without degrading planning target volume (PTV) coverage 10 , 11 , 12 , 13 , 14 . In the voluntary DIBH technique, patients are instructed verbally and/or visually to maintain their respiratory position during treatment delivery (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the respiratory tumor motion is reduced and the separation of the target volume from critical structures is increased. A number of previous studies reported the significant reduction of cardiac doses with DIBH 9 , 11 , 12 . For example, the comparison study with 17 breast cancer patients by Korreman et al (13) showed that the median heart volume receiving more than 50% of the prescription dose was reduced from 19.2% with free breathing (FB) to 1.9% with DIBH when the mean chest wall position with DIBH was 12.6 mm higher from that of FB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMRT has widened the horizons of radiation therapy due to its ability to conform radiation dose distributions to complex tumor target volumes while sparing nearby critical structures as much as physically possible. The use of IMRT to treat prostate cancer improves the overall survival and disease-free survival rates (3). Furthermore, compared with traditional three-dimensional conformal radiotherapy, IMRT improves normal tissue sparing in prostate cancer therapy, without compromising the dose delivered to the target (4).…”
Section: Introductionmentioning
confidence: 99%